Understanding the endometrium at menopause: A hysteroscopist's view - Milind Telang; Tanvir Tanvir (Wolters Kluwer Medknow Publications, 2021)
The risk of premalignant and malignant endometrial pathologies increases in the postmenopausal period. Dilatation and curettage fail to diagnose one in ten endometrial pathologies. Hysteroscopy is the gold standard to evaluate the endometrial cavity. Hysteroscopy can identify malignant or benign pathology with approximately 20% false-positive results. Hysteroscopy combined with biopsy increases the accuracy of diagnosis up to 100%. This pictorial review takes you through the hysteroscopic view of normal-looking postmenopausal atrophic uterus, cystic atrophy, benign endometrial pathologies, endometrial hyperplasia, endometrial cancer, tamoxifen-induced endometrial hyperplasia and histiocytic endometritis. The purpose of this pictorial review is to guide the operator in systematic evaluation of the endometrial cavity with special attention to the thickness of the endometrium, vascular architecture, location of the lesion and surface aberrations, which adds value to the diagnosis and management of endometrial pathologies.